IMPLEMENTASI TEORI ANTRIAN PADA TOKO ADI JAYA DIKECAMATAN GEDANGAN SIDOARJO - Liang Rosah Lina; Erna Andajani; Stefanus Budy Widjaja S. (Perpustakaan Universitas Surabaya, 2018)
This study aims to minimize customer complaints resulting from queue length and length of waiting time, reduce customers from queuing, analyze server (server) needs, and know what efforts can be used to reduce the length of the queue. So that the length of the queue can be minimized and can provide better service and performance.This research used M / M / 1 and M / M / 2 model to apply queuing theory method and assisted with SPSS 16.0 software as a basis to know the distribution to be used, then using POM Windows 3 software as base to analyze queue length, queue length in the system, time of service, and time of service within the existing system within the Adi Jaya store.The study found that of the three types of services and purchases owned by the Adijaya store. This store requires additional servers for the types of document printing services, Photo Print, and Photo Close Up. In addition to adding this server Adi Jaya store can make additional facilities to wait.